Brain Injury and Family Violence: Establishing a Tool to Support Clinical Practice - Kathryn Upton; Christine Thai; Vincent Oxenham; Toni D. Withiel; Caroline A. Fisher (Journal of Family Violence, 2026)
Abstract Objective Cognitive dysfunction often occurs as a result of acquired brain injury or psychological trauma from family violence. However, these less visible injuries are often overlooked by frontline professionals. Current screening tools for brain injury have been developed for the general population and do not align with best practice frameworks for identifying these issues in victim-survivors. This study aimed to use a modified Delphi approach to develop content for a brain injury and cognitive dysfunction screening tool for victim-survivors of family violence. Method A modified Delphi study was used to obtain consensus amongst experts on content for the screening tool over three iterative rounds. The expert panel consisted of participants from diverse backgrounds including neuropsychologists, social workers, medical professionals, family violence clinicians, Aboriginal peoples, and people with lived experience. Results Twenty-two participants responded over three discrete survey rounds (response rate: R1 n = 22, R2 n = 19, R3 n = 17). The expert panel endorsed 32 items relating to acquired brain injury, cognitive dysfunction, and psychological trauma for inclusion in the screening tool, and 16 of the 32 items were endorsed to comprise a short form of the screening tool. Six optional demographic items were also endorsed for inclusion in both forms of the screening tool. Conclusions Using a modified Delphi method, this study developed initial content for the Brain Injury and Cognition – Family Violence (BIC-FV) screening tool. Future research will include pilot studies to investigate the psychometric properties of the BIC-FV screening tool.